The Effect of Company Fundmentals and Macroeconomics Factors on Stock Prices in the 2019-2023 Period (A Study on Banking Companies in the Infobank15 Index) - Rafi, Izzan Ayman; Paksi, Girindra Mega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the factors that influence banking stock prices with large market capitalization, which impact the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange. The variables used include macroeconomic variables (interest rates) and company fundamental variables (ROA, PBV, DER). This research is quantitative and explanatory, using purposive sampling on 12 companies listed in the Infobank15 index for the 2019-2023 period. The analysis was conducted using multiple linear regression and classical assumption tests, including normality, multicollinearity, heteroscedasticity tests. The results show that PBV and interest rates have a significant positive effect on banking stock prices, while ROA and DER have no significant effect on banking stock price movements. This study recommends that investors focus more on interest rates and PBV indicators to predict banking stock price movements.